Positive electrode active material for secondary battery
By adding calcium dopant to the positive electrode active material of lithium composite oxide and applying grain boundary, the problems of volume changes, cracks and crystal structure collapse during charging and discharge are solved, and the life performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411499710.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-30
- Filing Date
- 2024-10-25
- Publication Date
- 2025-05-02
Smart Images

Figure HDA0005102261910000011 
Figure HDA0005102261910000012 
Figure HDA0005102261910000013
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a secondary battery, and more particularly, to positive electrode active material particles including lithium composite oxide particles and a coating material, and a positive electrode active material including the same. Background Art
[0002] With the development of portable mobile electronic devices such as smart phones, MP3 players, and tablet computers, the demand for secondary batteries capable of storing electric energy has increased explosively. In particular, with the emergence of electric vehicles, large and medium-sized energy storage systems, and portable devices that require high energy density, the demand for lithium secondary batteries is continuously increasing.
[0003] As a lithium composite oxide included in a positive electrode active material, a recently spotlighted material is lithium nickel manganese cobalt oxide Li(Ni x Co y Mn z )O2 (in this case, x, y, and z are atomic fractions of respective independent oxide constituent elements, 0 < x ≤ 1, 0 < y ≤ 1, 0 < z ≤ 1, and 0 < x + y + z ≤ 1). Compared with the positive electrode active material LiCoO2 that has been actively studied and used in the past, since this positive electrode active material is used at a high voltage, it has the advantage of high output capacity, and since the Co content is relatively low, it has the advantage of low price.
[0004] However, with the insertion and extraction of lithium ions during charge and discharge, such a lithium composite oxide is accompanied by volume changes. During charge and discharge, there are problems such as a sharp volume change in primary particles of the lithium composite oxide, or the generation of cracks in secondary particles with repeated charge and discharge, or the collapse of the crystal structure or crystal structure phase change.
[0005] In order to compensate for this disadvantage, as a positive electrode active material for a secondary battery, the demand for a nickel (Ni)-rich system - high nickel positive electrode active material in which the content of nickel (Ni) is 50 mol% or more based on the total content of transition metals other than lithium (Li) has started to increase. However, although such a nickel-rich positive electrode active material has the advantage of high energy density, with the increase in the Ni content, the structural instability due to Li / Ni cation mixing increases, physical fracture of internal particles due to microcracks, and accelerated electrolyte depletion, etc., there is a problem that the life characteristics deteriorate rapidly at room temperature and high temperature. Summary of the Invention
[0006] Technical Problem
[0007] The present invention aims to add calcium (Ca) as a dopant in a specific content and using a specific preparation method when preparing a positive electrode active material, thereby diffusing coating elements into the positive electrode active material particles and controlling the concentration of the coating elements on the surface of the positive electrode active material particles, and to improve the problems of the existing grain boundary coating method and improve the life performance of the battery by performing grain boundary coating between primary particles of lithium composite oxides.
[0008] Technical Solution
[0009] The positive electrode active material particles according to one embodiment of the present invention may include lithium composite oxide particles and a coating material containing a coating element. The above-mentioned lithium composite oxide particles may be secondary particles formed by agglomeration of two or more primary particles. The above-mentioned coating material may be contained on the surface of the above-mentioned secondary particles. The above-mentioned coating material may be contained in the grain boundaries between the above-mentioned primary particles. Calcium may be contained in the above-mentioned positive electrode active material particles. The content X of calcium contained in the above-mentioned positive electrode active material may be 0.003 mol%≤X≤0.03 mol%.
[0010] As one embodiment, the above-mentioned positive electrode active material particles may include the above-mentioned coating elements. For the surface of the above-mentioned positive electrode active material particles, the average concentration Y of the above-mentioned coating elements measured by energy profiling-energy dispersive X-ray spectroscopy (EP-EDS) may be 32 atomic percent ≤ Y ≤ 37 atomic percent. The above-mentioned energy profiling-energy dispersive X-ray spectroscopy uses an electron beam irradiated with an accelerating voltage of 3 kV to measure the average concentration of the elements from the surface of the above-mentioned positive electrode active material particles to the depth of penetration of the above-mentioned electron beam.
[0011] As one embodiment, the coating element may be cobalt (Co), and the coating material may be cobalt oxide.
[0012] As one embodiment, the above-mentioned positive electrode active material particles may contain cobalt. For the surface of the above-mentioned positive electrode active material particles, the average concentration Y of cobalt measured by energy analysis-energy dispersive X-ray spectrometry may be 32 atomic percent ≤ Y ≤ 37 atomic percent. The above-mentioned energy analysis-energy dispersive X-ray spectrometry uses an electron beam irradiated with an accelerating voltage of 3 kV to measure the average concentration of the element from the surface of the above-mentioned positive electrode active material particles to the depth of penetration of the above-mentioned electron beam.
[0013] As one embodiment, the calcium may be contained in the positive electrode active material particles in the form of calcium oxide on the surface of the secondary particles.
[0014] As one embodiment, the calcium may be contained in the positive electrode active material particles in the form of calcium oxide in the grain boundaries between the primary particles.
[0015] The positive electrode active material according to one embodiment of the present invention may include a plurality of the positive electrode active material particles described above.
[0016] As one embodiment, the positive electrode active material contained in the above-mentioned positive electrode active material can be the above-mentioned first positive electrode active material particles with an average particle size (D50) of 8μm or more, and the above-mentioned positive electrode active material can also include second positive electrode active material particles with an average particle size (D50) of 7μm or less.
[0017] As one embodiment, when the weight of the first positive electrode active material particles is w1 and the weight of the second positive electrode active material particles is w2, w1 / w2 may be 1.5 to 9.0 or less.
[0018] A positive electrode according to one embodiment of the present invention includes the positive electrode active material particles described above.
[0019] A secondary battery according to one embodiment of the present invention includes the above-mentioned positive electrode active material particles.
[0020] Effects of the Invention
[0021] One effect of the present invention is that the battery life performance can be improved by controlling the content of the coating element on the surface of the positive electrode active material particles and performing grain boundary coating in a manner that improves the problems of the conventional grain boundary coating method. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The calcium doping method according to an embodiment of the present invention is shown.
[0023] Figure 2 The cross-sectional EDS images of the positive electrode active material particles of the comparative examples and the examples of the present invention are shown.
[0024] Figure 3 The results of X-ray diffraction (XRD) analysis of the positive electrode active material particles according to the examples of the present invention using CuKα rays are shown. DETAILED DESCRIPTION
[0025] Expressions such as "comprising" and the like used in this specification should be understood as open-ended terms implying the possibility of including other structures.
[0026] The terms "preferred" and "preferably" used in this specification refer to embodiments of the present invention that can provide specified advantages under specified circumstances. However, other embodiments are not intended to be excluded from the scope of the present invention.
[0027] Furthermore, unless otherwise indicated in the context, singular forms used in the specification and the appended claims may be intended to include plural forms as well.
[0028] On the other hand, the following technical features relate to an embodiment for achieving the above-mentioned desired effects of the present invention.
[0029] That is, the positive electrode active material particles according to one embodiment of the present invention include the technical features according to one embodiment described below, and thus when applied to a secondary battery, the battery characteristics can be significantly improved.
[0030] The present invention relates to positive electrode active material particles for secondary batteries and positive electrode active materials containing a plurality of the particles. The type of secondary battery of the present invention is not limited, as long as it is a battery that can convert external electrical energy into chemical energy and store it for reuse. As a more preferred embodiment, the present invention may relate to positive electrode active materials for lithium ion secondary batteries.
[0031] In nickel-based positive electrode active materials, especially high-nickel (High-Ni) positive electrode active materials, coating can improve battery performance such as life and resistance. In particular, grain boundary coating between primary particles can maximize this advantage.
[0032] For this grain boundary coating, a coating material is diffused into the interior of the particles at a specific heat treatment temperature. However, there are problems caused by changing the heat treatment temperature for grain boundary coating and a problem of reduced battery performance due to changes in physical properties such as deformation of primary particles.
[0033] The present invention can improve the problem of grain boundary coating by adding calcium as a dopant in a specific content and using a specific preparation method, so that the coating elements, especially cobalt, can be diffused into the interior of the positive electrode active material particles and coated on the grain boundaries between the primary particles, and the battery performance can be improved by adjusting the content of the coating elements on the surface of the positive electrode active material particles.
[0034] One positive electrode active material particle according to one embodiment of the present invention includes one lithium composite oxide particle.
[0035] Furthermore, the lithium composite oxide particles are secondary particles formed by agglomeration of two or more primary particles.
[0036] Furthermore, the positive electrode active material particles may include a coating material including a coating element.
[0037] On the other hand, in the present specification, the lithium composite oxide particles are distinguished from the coating material.
[0038] When the lithium composite oxide particles according to one embodiment of the present invention are subjected to coating treatment, part of the coating element may be present in the lattice structure of the primary particles contained in the lithium composite oxide particles. This means that the coating element is doped into the lithium composite oxide particles, and the lithium composite oxide particles are defined as including all the doped regions as described above.
[0039] On the other hand, when the lithium composite oxide particles of one embodiment of the present invention are subjected to coating treatment, part of the coating elements may form coating substances. Such coating substances may exist on the surface of the secondary particles of the lithium composite oxide particles and / or in the grain boundaries between the primary particles of the lithium composite oxide.
[0040] In this case, the grain boundary between primary particles refers to a region including both the space between the primary particles and the surface of the primary particles.
[0041] That is, in this specification, the doped region in the lattice structure of the lithium composite oxide primary particles of the positive electrode active material particles, the surface of the lithium composite oxide secondary particles, and the grain boundary region between the lithium composite oxide primary particles are all different regions.
[0042] On the other hand, in this specification, "element", "calcium (Ca)", and "cobalt (Co)" are interpreted as meanings including both a zero-valent state and an ion state.
[0043] As one embodiment, the lithium composite oxide particles may contain nickel.
[0044] As one embodiment, the lithium composite oxide particles may further include one or more selected from the group consisting of cobalt, aluminum (Al), and manganese (Mn).
[0045] As one embodiment, the lithium composite oxide particles may be represented by the following Chemical Formula 1.
[0046] Chemical formula 1:
[0047] Li a Ni x Co y M 1-x-y O2
[0048] In the above Chemical Formula 1, M is selected from the group consisting of Zr, Mn, Al, B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.9≤a≤1.2, 0.5≤x≤1.0, 0.0≤y≤0.4, and 0.0≤1-xy≤0.4.
[0049] As one embodiment, the lithium composite oxide particles may be represented by the following Chemical Formula 1-1.
[0050] Chemical formula 1-1:
[0051] Li a’ Ni x’ Co y’ M1 z’ M2 1-x’-y’-z’ O2
[0052] In the above chemical formula 1-1, M1 is Al or Mn, M2 is selected from the group consisting of Zr, B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.9≤a'≤1.2, 0.5≤x'≤1.0, 0.0≤y'≤0.4, 0.0≤z'≤0.4, 0.0≤1-x'-y'-z'≤0.4.
[0053] As one embodiment, in the above Chemical Formula 1 and / or Chemical Formula 1-1, a and / or a' representing the molar percentage of lithium relative to the total molar percentage of transition metals other than lithium may be greater than 0.9, greater than 1.0, less than 1.2, less than 1.1, or less than 1.05.
[0054] As one embodiment, in the above Chemical Formula 1 and / or Chemical Formula 1-1, x and / or x' representing the molar percentage of nickel relative to the total molar percentage of transition metals other than lithium may be 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. In particular, it may be a high nickel oxide in which x and / or x' is 0.8 or more or 0.9 or more.
[0055] As one embodiment, in the above Chemical Formula 1 and / or Chemical Formula 1-1, y and / or y' representing the molar percentage of cobalt relative to the total molar percentage of transition metals other than lithium may be 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.
[0056] The crystal structure of the lithium composite oxide particles according to one embodiment of the present invention may be hexagonal α-NaFeO 2 (R-3m space group).
[0057] Next, the positive electrode active material particles according to one embodiment of the present invention include a coating material containing a coating element.
[0058] As an example, the coating material may be a coating oxide.
[0059] As one embodiment, the coating material may be represented by the following Chemical Formula 2.
[0060] Chemical formula 2:
[0061] Li p M3 q O r
[0062] In the above chemical formula 2, M3 is one or more selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd and Nd, and 0≤p≤10,0 <q≤8,2≤r≤13。
[0063] As an example, in the above chemical formula 2, M3 refers to a coating element, and the above coating oxide may be an oxide in which lithium and an element represented by M3 are combined, or an oxide of M3.
[0064] As an example, the coating oxide may be Li p Co q O r , Li p W q O r , Li p Zr q O r , Li p Ti q O r , Li p Ni q O r , Li p Al q O r , Li p Mo q O r 、Co q O r 、Al q O r , W q O r 、Zr q O r 、Ti q O r , B q O r , Li p (W / Ti) q O r , Li p (W / Zr) q O r , Li p (W / Ti / Zr) q O r , Li p(W / Ti / B) q O r , but not limited to this.
[0065] The coating oxide may include a concentration gradient portion where the molar concentration of the element contained in the coating oxide changes. As an example, when the coating oxide includes lithium, the molar concentration of lithium may change. Also, as an example, the molar concentration of one or more of M3 contained in the coating oxide may change.
[0066] As one embodiment, the coating material may be contained on the surface of the lithium composite oxide secondary particles and in the grain boundaries between the lithium composite oxide primary particles.
[0067] On the other hand, as one embodiment, the coating element may be contained in a coating substance contained on the surface of the lithium composite oxide secondary particle.
[0068] Furthermore, as one embodiment, the coating element may be contained in a coating substance contained in a grain boundary between primary particles of the lithium composite oxide.
[0069] Also, as one embodiment, the coating element may be doped and included in the lattice structure of the lithium composite oxide primary particle instead of the coating substance.
[0070] As a more preferred embodiment, the above-mentioned positive electrode active material particles may contain the above-mentioned coating elements. For the surface of the above-mentioned positive electrode active material particles, the average concentration Y of the above-mentioned coating elements measured by energy analysis-energy dispersive X-ray spectrometry can be greater than 32 atomic percent, greater than 33 atomic percent, greater than 34 atomic percent, greater than 35 atomic percent, less than 37 atomic percent or less than 36 atomic percent. The above-mentioned energy analysis-energy dispersive X-ray spectrometry uses an electron beam irradiated with an accelerating voltage of 3 kV to measure the average concentration of the element from the surface of the above-mentioned positive electrode active material particles to the depth at which the above-mentioned electron beam penetrates.
[0071] The present invention can improve the battery life performance by adding calcium as a dopant in a specific content and using a specific preparation method, thereby diffusing the coating element into the positive electrode active material particles, and adjusting the concentration of the coating element on the surface of the positive electrode active material particles to 32 atomic percent ≤ Y ≤ 37 atomic percent.
[0072] As a more preferred embodiment, the coating element may be cobalt, and the coating substance may be cobalt oxide.
[0073] On the other hand, in the present specification, a coating oxide is an oxide containing a coating element and includes all cases where other elements are further contained, and a cobalt oxide is an oxide containing cobalt and includes all cases where other elements are further contained.
[0074] As an example, the cobalt oxide may be Li p Co q O r 、Co q O r , and / or LCO-like structures are included. On the other hand, the LCO-like structure is an intermediate that can exist in the process of forming cobalt oxide of LiCoO2, for example, it can be amorphous or spinel structure.
[0075] As one embodiment, the cobalt oxide may be included on the surface of the lithium composite oxide secondary particles and in the grain boundaries between the lithium composite oxide primary particles.
[0076] On the other hand, as one embodiment, cobalt may be contained in cobalt oxide contained on the surface of the lithium composite oxide secondary particle.
[0077] Furthermore, as one embodiment, cobalt may be contained in a coating material contained in a grain boundary between primary particles of the lithium composite oxide.
[0078] Also, as one embodiment, cobalt may be doped and included in the lattice structure of the lithium composite oxide primary particles instead of being a coating material.
[0079] As a more preferred embodiment, the above-mentioned positive electrode active material particles may contain the above-mentioned cobalt. For the surface of the above-mentioned positive electrode active material particles, the average concentration Y' of the above-mentioned cobalt measured by energy analysis-energy dispersive X-ray spectrometry can be greater than 32 atomic percent, greater than 33 atomic percent, greater than 34 atomic percent, greater than 35 atomic percent, less than 37 atomic percent or less than 36 atomic percent. The above-mentioned energy analysis-energy dispersive X-ray spectrometry uses an electron beam irradiated with an accelerating voltage of 3 kV to measure the average concentration of the element from the surface of the above-mentioned positive electrode active material particles to the depth at which the above-mentioned electron beam penetrates.
[0080] The present invention can improve the battery life performance by adding calcium as a dopant in a specific content and using a specific preparation method, thereby diffusing cobalt into the positive electrode active material particles and adjusting the cobalt concentration on the surface of the positive electrode active material particles to 32 atomic percent ≤ Y ≤ 37 atomic percent.
[0081] Next, calcium is added as a dopant so that it can be contained in the positive electrode active material particles.
[0082] As one embodiment, the calcium may be present in one or more regions selected from the group consisting of a doped region in the lattice structure of the lithium composite oxide primary particles, a surface of the lithium composite oxide secondary particles, and a grain boundary region between the lithium composite oxide primary particles.
[0083] As one embodiment, when present in the grain boundary region between primary particles of the lithium composite oxide, it may exist as calcium ions themselves.
[0084] As one embodiment, when present on the surface of lithium composite oxide secondary particles and in the grain boundary region between lithium composite oxide primary particles, it may be present in the form of calcium oxide, that is, various forms of oxides containing calcium. As an example, it may be present in the form of amorphous calcium composite oxide.
[0085] As an embodiment, the calcium content X contained in the positive electrode active material particles may be 0.003 mol% or more, 0.005 mol% or more, 0.03 mol% or less, or 0.025 mol% or less. The present invention can include the above-mentioned content of calcium in the positive electrode active material particles, so that the coating elements, especially cobalt, diffuse into the interior of the positive electrode active material particles and are coated on the grain boundaries between the primary particles of the lithium composite oxide, while controlling the concentration of the coating elements, especially cobalt, on the surface of the positive electrode active material particles, thereby improving the battery performance.
[0086] The positive electrode active material according to one embodiment of the present invention may include a plurality of the positive electrode active material particles described above.
[0087] The positive electrode active material according to one embodiment of the present invention may be in a unimodal form, and the average particle size (D50) of the positive electrode active material particles may be 1 μm to 30 μm, more preferably, 8 μm to 20 μm.
[0088] In this manual, D 50 It is the particle size at 50% of the cumulative distribution of particle sizes according to the area, and can be measured by a laser diffraction method. Specifically, the powder to be tested can be dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device to measure the difference in diffraction patterns according to the particle size when the particles pass through a laser beam, thereby calculating the particle size distribution.
[0089] As one embodiment, when the positive electrode active material is in a bimodal form, the lithium composite oxide particles may be secondary particles formed by agglomeration of a plurality of primary particles, and the primary particles may include one or more crystallites.
[0090] As one embodiment, the secondary particles may be in the form of multiple particles or polycrystalline particles including two or more primary particles.
[0091] As a more preferred embodiment, the grain boundary density of the secondary particles calculated by the following formula 1 may be 0.50 or more, 0.60 or more, 0.70 or more, 0.80 or more, 0.90 or more, or 0.95 or more.
[0092] Formula 1:
[0093] Grain boundary density = the number of grain boundaries between the primary particles located on the straight line / the number of the primary particles located on the straight line
[0094] The above-mentioned “grain boundary density” is calculated from the primary particles and grain boundaries between the primary particles located on a straight line passing through the center of the secondary particle and crossing along the minor axis direction in the cross-sectional image of the above-mentioned particle photographed by a scanning electron microscope (SEM).
[0095] For example, in the case of a non-agglomerated single particle composed of a single primary particle, the grain boundary density calculated by the above formula 1 may be 0. Also, when two primary particles are agglomerated, the grain boundary density calculated by the above formula 1 may be 0.5.
[0096] In this case, the above-mentioned grain boundary density refers to the average value of corresponding straight lines when 10 straight lines are drawn arbitrarily.
[0097] Furthermore, as another more preferred embodiment, the positive electrode active material particles contained in the above-mentioned positive electrode active material may be the above-mentioned first positive electrode active material particles having an average particle size (D50) of more than 8 μm, and the above-mentioned positive electrode active material may be a bimodal form further comprising second positive electrode active material particles having an average particle size (D50) of less than 7 μm.
[0098] As one embodiment, in the case where the positive electrode active material is in a bimodal form, when the weight of the first positive electrode active material particles contained in the positive electrode active material is set to w1, and the weight of the second positive electrode active material particles is set to w2, w1 / w2 may be 1.5 to 9.0 or 2.0 to 4.0. The invention can increase the energy density by using small particles in the pores between large particles in the bimodal positive electrode active material having such a mixing ratio, and can solve the problem of reduced battery characteristics caused by changes in the average particle size deviation between large particles and small particles.
[0099] As one embodiment, when the positive electrode active material of the present invention is in a bimodal form, the first lithium composite oxide particles in the above-mentioned first positive electrode active material particles as large particles can be secondary particles formed by agglomeration of primary particles, and the primary particles of the above-mentioned first lithium composite oxide particles can contain more than one microcrystal.
[0100] As one embodiment, the secondary particles of the first lithium composite oxide particles may be in the form of multiple particles or polycrystalline particles including a plurality of primary particles.
[0101] As one embodiment, the grain boundary density of the first lithium composite oxide particles calculated by the above formula 1 may be 0.95 or more.
[0102] As one embodiment, the second lithium composite oxide particles in the second cathode active material particles as small particles may be in the form of a single particle including one primary particle, and may be in the form of a single crystal when the primary particle consists of one crystallite.
[0103] As another embodiment, the second lithium composite oxide particles may be in the form of multiple particles or polycrystalline particles including two or more primary particles.
[0104] As one embodiment, the grain boundary density of the second lithium composite oxide particles calculated by Formula 1 may be 0.98 or less, 0.95 or less, 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less.
[0105] The positive electrode active material particles and the preparation method of the positive electrode active material according to one embodiment of the present invention are not limited as long as they have the above-mentioned technical features. However, as a more preferred embodiment, they can be prepared as follows.
[0106] First, a hydroxide precursor can be prepared.
[0107] Next, the prepared hydroxide precursor may be heat-treated to prepare an oxide precursor. In this case, the heat-treatment temperature may be 300°C to 500°C.
[0108] Next, the lithium composite oxide may be prepared by mixing the prepared oxide precursor and the lithium compound and performing a heat treatment. In this case, the heat treatment temperature may be 750°C to 850°C.
[0109] Next, the lithium composite oxide that has been heat treated can be cleaned by adding a cleaning solution, and a cobalt aqueous solution and a calcium aqueous solution are added to stir and then dried (refer to Figure 1 ).
[0110] Next, the dried product may be heat-treated to prepare a positive electrode active material. In this case, the heat treatment temperature may be 680°C to 720°C.
[0111] The positive electrode active material particles and the preparation method of the positive electrode active material according to one embodiment of the present invention can simultaneously perform cobalt wet coating and calcium wet doping in the cleaning step of the lithium composite oxide, so that the cobalt diffuses into the interior of the particles and is coated on the grain boundaries between the primary particles, while adjusting the content of the coating elements on the surface of the secondary particles of the lithium composite oxide to improve the battery performance.
[0112] On the other hand, the technical characteristics of the positive electrode active material particles may be related to the average technical characteristics of a plurality of positive electrode active material particles contained in the positive electrode active material.
[0113] On the other hand, the meaning of “≤”, “above” or “below” described in the present invention can be replaced by the meaning of “<”, “greater than” or “less than”.
[0114] A positive electrode according to one embodiment of the present invention includes the positive electrode active material particles described above.
[0115] In addition to using the positive electrode active material particles, the positive electrode may have a known structure and be prepared according to a known preparation method. The binder, conductive material and solvent are not particularly limited as long as they can be used for the positive electrode collector of a secondary battery.
[0116] A secondary battery according to one embodiment of the present invention includes the above-mentioned positive electrode active material particles.
[0117] Specifically, the secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and an electrolyte between the positive electrode and the negative electrode, but there is no particular limitation as long as it can be used as a secondary battery.
[0118] Hereinafter, embodiments of the present invention will be described in more detail.
[0119] Preparation of positive electrode active material
[0120] Example
[0121] (a) Preparation of hydroxide precursor
[0122] A large hydroxide particle precursor and a small hydroxide particle precursor designed with an atomic ratio of Ni:Co:Al=95:4:1 (atomic percentage) were synthesized by a co-precipitation method using nickel sulfate, cobalt sulfate, and aluminum sulfate.
[0123] (b) Preparation of oxide precursors
[0124] The synthesized large hydroxide particle precursor and small hydroxide particle precursor were heated at a rate of 2° C. per minute and sintered at 400° C. for 6 hours for oxidation to be converted into large oxide particle precursor and small oxide particle precursor, respectively.
[0125] The average particle size (D50) of the above-mentioned large oxide particle precursor is 15.0 μm, and the average particle size (D50) of the above-mentioned small oxide particle precursor is 3.0 μm.
[0126] (c) Preparation of positive electrode active material
[0127] The above-mentioned large oxide particle precursor and small oxide particle precursor are weighed so that their weight ratio is 70:30, and then LiOH (Li / (Ni+Co+Al) molar ratio = 1.05) is added and mixed, and then the temperature is increased to 800°C at a rate of 2°C per minute in a sintering furnace while maintaining an O2 atmosphere and heat treated for 12 hours to prepare an intermediate product.
[0128] Distilled water was added to the intermediate product, and 1.5 weight percent of NaOH was added relative to the lithium composite oxide. Then, 5.0 weight percent of cobalt sulfate aqueous solution was added so that the amount of cobalt from the cobalt sulfate aqueous solution was 3.0 mole percent relative to the metal elements (Ni+Co+Al) other than lithium in the intermediate product, and 0.5 weight percent of calcium nitrate aqueous solution was added so that the amount of calcium from the calcium nitrate aqueous solution was 0.01 mole percent relative to the metal elements (Ni+Co+Al) other than lithium in the intermediate product, and the surface of the intermediate product was coated with cobalt while stirring. After the reaction was completed, it was dried at a temperature of 120°C for 12 hours.
[0129] The dried product was heated to 700° C. at a rate of 2° C. per minute in a calcining furnace while maintaining an O 2 atmosphere, and heat-treated at 700° C. for 12 hours to obtain a bimodal positive electrode active material.
[0130] Example 2
[0131] The positive electrode active material was obtained in the same manner as in Example 1, except that 0.5 weight percent of calcium nitrate aqueous solution was added in step (c) so that the amount of calcium derived from the calcium nitrate aqueous solution was 0.02 mole percent relative to the metal elements (Ni+Co+Al) other than lithium in the above intermediate product.
[0132] Example 3
[0133] The positive electrode active material was obtained in the same manner as in Example 1, except that 0.5 weight percent of calcium nitrate aqueous solution was added in step (c) so that the amount of calcium derived from the calcium nitrate aqueous solution was 0.03 mole percent relative to the metal elements (Ni+Co+Al) other than lithium in the above intermediate product.
[0134] Comparative Example 1
[0135] A positive electrode active material was obtained in the same manner as in Example 1, except that the 0.5 weight percent calcium nitrate aqueous solution was not added in step (c).
[0136] Comparative Example 2
[0137] The positive electrode active material was obtained in the same manner as in Example 1, except that 0.5 weight percent of calcium nitrate aqueous solution was added in step (c) so that the amount of calcium derived from the calcium nitrate aqueous solution was 0.33 mole percent relative to the metal elements (Ni+Co+Al) other than lithium in the above intermediate product.
[0138] Preparation of lithium secondary batteries
[0139] The positive electrode slurry was prepared by dispersing 92 weight percent of the positive electrode active material of the above embodiment and the comparative example, 4 weight percent of artificial graphite, and 4 weight percent of polyvinylidene fluoride (PVDF) binder into 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was evenly coated on an aluminum film with a thickness of 15 μm and vacuum dried at a temperature of 135° C. to prepare a positive electrode for a lithium secondary battery.
[0140] For the above-mentioned positive electrode, lithium foil was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separator, and a button cell was prepared using an electrolyte containing 1.15 M LiPF6 in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.
[0141] Experimental Example 1: Analysis of Surface Cobalt Content
[0142] For the surface of the positive electrode active material particles of the above-mentioned embodiments and comparative examples, the average concentration of the above-mentioned cobalt measured by energy analysis-energy dispersive X-ray spectrometry is shown in the following Table 1. The above-mentioned energy analysis-energy dispersive X-ray spectrometry uses an electron beam irradiated with an accelerating voltage of 3 kV to measure the average concentration of the element from the surface of the above-mentioned positive electrode active material particles to the depth at which the above-mentioned electron beam penetrates.
[0143] The energy analysis-energy dispersive X-ray spectroscopy measurement is performed by scanning the surface of the positive electrode active material particles with an electron beam accelerated at a voltage of 3 kV using a scanning electron microscope (Scanning Electron Microscope, SEM; Hitachi Co.) and analyzing the EDS component.
[0144] Table 1
[0145] Doping content 3kV Co concentration unit Mole Percent Atomic Percent Example 1 0.01 35.5 Example 2 0.02 35.1 Example 3 0.03 34.4 Comparative Example 1 0 37.9 Comparative Example 2 0.33 33 3
[0146] Experimental Example 2
[0147] The results of measuring the battery characteristics of the lithium secondary batteries of the above-described Examples and Comparative Examples are shown in Table 2 below.
[0148] The charge / discharge capacity was measured by a charge / discharge test using an electrochemical analyzer (Toyo, Toscat-3100) at a temperature of 25° C. and a voltage range of 3.0 V to 4.25 V at a discharge rate of 0.2 C to measure the initial charge capacity and initial discharge capacity, and the efficiency was calculated.
[0149] The life span was determined by charging and discharging the same lithium secondary battery 50 times at 45°C and a driving voltage range of 3.0V to 4.3V at 1C / 1C, and then measuring the ratio of the discharge capacity at the 50th cycle to the initial discharge capacity (cycle capacity retention).
[0150] Table 2
[0151] Charging capacity Discharge capacity efficiency life unit mAh / g mAh / g % % Example 1 238.9 212.0 88.8% 83.5% Example 2 239.2 211.6 88.5% 81.5% Example 3 239.2 212.0 88.6% 80.3% Comparative Example 1 237.8 209.9 88.3% 78.4% Comparative Example 2 238.4 211.4 88.7% 77.8%
[0152] From the above Table 2, it can be confirmed that the charge-discharge capacity and life characteristics of the Examples are significantly improved compared with the Comparative Examples.
[0153] Experimental Example 3: Cross-sectional EDS image measurement
[0154] The cross-sectional EDS images of the large particles included in the positive electrode active materials of the above-mentioned Examples and Comparative Examples are shown in FIG. Figure 2 middle.
[0155] according to Figure 2 It can be confirmed that cobalt and calcium diffuse into the positive electrode active material particles by calcium wet coating, so that the cobalt concentration on the surface of the positive electrode active material particles is adjusted.
[0156] Experimental Example 4: XRD measurement
[0157] The results of X-ray diffraction analysis of the positive electrode active materials of the above-mentioned Examples and Comparative Examples using CuKα rays are shown in Figure 3 middle.
[0158] In the present invention, X-ray diffraction analysis is performed by using Cu Kα radiation The measurement was performed using a Bruker D8 Advance diffractometer at a step size (° / step) of 0.01° / step and a measurement time of 0.1 s / step.
[0159] according to Figure 3 Since the intensity of the Co-rich peak decreases with the increase of the added calcium content, it can be confirmed that calcium is doped into the primary particle lattice structure.
Claims
1. A positive electrode active material particle, comprising a lithium composite oxide particle and a coating material containing a coating element, characterized in that: The lithium composite oxide particles are secondary particles formed by agglomeration of two or more primary particles. The coating material is contained on the surface of the secondary particles. The coating material is contained in the grain boundaries between the primary particles. Calcium is contained in the positive electrode active material particles. The content X of calcium contained in the positive electrode active material particles is 0.003 mol %≤X≤0.03 mol %.
2. The positive electrode active material particle according to claim 1, characterized in that: For the surface of the above-mentioned positive electrode active material particles, the average concentration Y of the above-mentioned coating elements measured by energy analysis-energy dispersive X-ray spectrometry is 32 atomic percent ≤ Y ≤ 37 atomic percent. The above-mentioned energy analysis-energy dispersive X-ray spectrometry uses an electron beam irradiated with an accelerating voltage of 3 kV to measure the average concentration of the elements from the surface of the above-mentioned positive electrode active material particles to the depth of penetration of the above-mentioned electron beam.
3. The positive electrode active material particle according to claim 1, characterized in that: The coating element is cobalt, and the coating substance is cobalt oxide.
4. The positive electrode active material particle according to claim 1, characterized in that: The positive electrode active material particles contain cobalt. For the surface of the above-mentioned positive electrode active material particles, the average concentration Y of cobalt measured by energy analysis-energy dispersive X-ray spectrometry is 32 atomic percent ≤ Y ≤ 37 atomic percent. The above-mentioned energy analysis-energy dispersive X-ray spectrometry uses an electron beam irradiated with an accelerating voltage of 3 kV to measure the average concentration of elements from the surface of the above-mentioned positive electrode active material particles to the depth at which the above-mentioned electron beam penetrates.
5. The positive electrode active material particle according to claim 1, characterized in that: The calcium is contained in the positive electrode active material particles in the form of calcium oxide on the surface of the secondary particles.
6. The positive electrode active material particle according to claim 1, characterized in that: The calcium is contained in the positive electrode active material particles in the form of calcium oxide in the grain boundaries between the primary particles.
7. A positive electrode active material, characterized in that Contains a plurality of positive electrode active material particles according to claim 1.
8. The positive electrode active material according to claim 7, characterized in that The positive electrode active material particles are first positive electrode active material particles having an average particle size D50 of 8 μm or more. The second positive electrode active material particles having an average particle size D50 of 7 μm or less are also included.
9. The positive electrode active material according to claim 8, characterized in that When the weight of the first positive electrode active material particles is w1 and the weight of the second positive electrode active material particles is w2, w1 / w2 is 1.5 to 9.0 or less.
10. A positive electrode, characterized in that: Contains the positive electrode active material particles according to claim 1.
11. A secondary battery, characterized in that: Contains the positive electrode active material particles according to claim 1.